Exploring the Implementation and Impact of Mindful Parenting in Indonesia: A Scoping Review - Dinie Ratri Desiningrum; Yeniar Indriana; Darosy Endah Hyoscyamina; Milcha Fakhria; Abidah Salma Shalihah; Hasna Luthfia Zaim (Universitas Muhammadiyah Surakarta, 2024)
The implementation of mindful parenting in Indonesia is increasingly gaining attention in the context of child development and family well-being. This research aims to provide a comprehensive overview of mindful parenting practices in Indonesia, along with their impacts. The method employed in this study was a scoping review. Several steps were undertaken in this scoping process following the PRISMA-ScR guidelines (PRISMA Extension for Scoping Reviews). The literature search was conducted on Portal Garuda, SINTA, DOAJ, Google Scholar and Semantic Scholar. Inclusion criteria consisted in this research, and 16 articles were selected for full review. Those 16 journal articles were categorized into four characteristics: (1) the implementation of mindful parenting; (2) the effects of mindful parenting; (3) mindful parenting related to parenting children with special needs; and (4) the relationship between mindful parenting and other variables in various context. The results of the scoping review indicate that Mindful Parenting (1) reduces anxiety, parenting stress, and psychological burden for mothers; (2) improves subjective well-being, self-esteem, and cognitive abilities in parents; (3) is associated with Baumrind's parenting styles;(4) creates two key dimensions in parenting—being present and disciplining with awareness; (5) promotes children's independence and moral behavior; and (6) increases father involvement. The grand theories used in most of these articles are primarily based on Duncan and Bögels' theories. This scoping review demonstrates the significant benefits of developing and implementing mindful parenting tailored to the characteristics of Indonesians, making it possible to be implemented broadly.